Metabolic dysfunction and altered mitochondrial dynamics in the utrophin-dystrophin deficient mouse model of duchenne muscular dystrophy. - Meghna Pant; Danesh H Sopariwala; Naresh C Bal; Jeovanna Lowe; Dawn A Delfín; Jill Rafael-Fortney; Muthu Periasamy (PLoS ONE, 2015)
The utrophin-dystrophin deficient (DKO) mouse model has been widely used to understand the progression of Duchenne muscular dystrophy (DMD). However, it is unclear as to what extent muscle pathology affects metabolism. Therefore, the present study was focused on understanding energy expenditure in the whole animal and in isolated extensor digitorum longus (EDL) muscle and to determine changes in metabolic enzymes. Our results show that the 8 week-old DKO mice consume higher oxygen relative to activity levels. Interestingly the EDL muscle from DKO mouse consumes higher oxygen per unit integral force, generates less force and performs better in the presence of pyruvate thus mimicking a slow twitch muscle. We also found that the expression of hexokinase 1 and pyruvate kinase M2 was upregulated several fold suggesting increased glycolytic flux. Additionally, there is a dramatic increase in dynamin-related protein 1 (Drp 1) and mitofusin 2 protein levels suggesting increased mitochondrial fission and fusion, a feature associated with increased energy demand and altered mitochondrial dynamics. Collectively our studies point out that the dystrophic disease has caused significant changes in muscle metabolism. To meet the increased energetic demand, upregulation of metabolic enzymes and regulators of mitochondrial fusion and fission is observed in the dystrophic muscle. A better understanding of the metabolic demands and the accompanied alterations in the dystrophic muscle can help us design improved intervention therapies along with existing drug treatments for the DMD patients.